Changes in somatic build, body composition and motor performance of young female volleyball players in the preparatory period for the season - Sieroń, Adrian; Pietraszewska, Jadwiga (Journal of Education, Health and Sport, 2018)
Introduction. Volleyball is one of the most popular sports in Poland. In recent years, there is a growing interest in this discipline among young people. It is important for researchers and trainers to find the factors that determine the achievement of high scores among youth athletes. Monitoring morpho-functional changes in the training cycle is an important method to assess the impact of training on a young, developing athlete’s body. Materials and methods. 27 volleyball players aged 16-17 participated in the study. The measurements included basic somatic features: height and body mass, BMI and in addition, motor tests were carried out. Body composition was assessed by bioelectrical impedance analysis (BIA). The tests were realized twice over two months. Results and summary. The results show positive changes in body composition and improvement of results in fitness tests at the end of the preparatory period.